POLITIK HUKUM UNDANG-UNDANG NOMOR 8 TAHUN 1981 TENTANG KITAB HUKUM ACARA PIDANA - Lonna Yohanes Lengkong (to-ra, 2019)
Abstract In Indonesia, provisions for both civil and criminal procedural law a still applied referred to the Dutch colonial legislation, such as HIR and RBg. The spirit of independence and the mandate of the State Policy Outlines stipulated in MPR Decree No. RI. IV / MPR RI / 1978 dated March 22, 1978, the Indonesian legal politics recognised legislation in accordance with the spirit of independence of Indonesia and the Pancasilais. regime under The new order whose played a major role in giving birth to Law No. 8 of 1981, despite the reluctance of the authorities to universally recognise human rights by applying subversive laws at that time Keywords: the new order politic of law, the criminal procedure code.